Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Keaktifan Belajar Siswa pada Materi Sumber Energi di Kelas IV SD IT Ar-Roudloh Batang - Mustanfidah, Ayyum; Nalim, Nalim (LP2M STAI Darul Kamal NW Kembang Kerang, 2024)
This research aims to determine the effect of theteams games tournament (TGT) type cooperative learning model on students' active learning in energy sources material in classIV SDIT Ar Roudloh Batang. This research is experimentalresearch with a quantitative approach. The sample in this study was students in class IVB and IVC, with class IVB as a controlclass totaling 28 students and class IVC as an experimentalclass totaling 28 students. Data collection techniques were carried out using questionnaires, observation anddocumentation. And data analysis using the Mann Whitney testto test the hypothesis. The results showed that the experimentalclass had a higher average post-test score than the control class. Based on the Mann Whitney test, a significance value of 0.00 <0.05 is obtained, which means Ho is rejected and H1 isaccepted. So it can be concluded that the application of theteams games tournament type cooperative learning model onenergy source material is effective on student learning activity in class IV SDIT Ar Roudloh Batang.